The value of confessio iudicilias in Mitis Iudex Dominus Iesus - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2016)
Taking up the value of confessio iudicialis for declaring a marriage null and voit, the author begins his reflections with a look at different forms of declarations of the parties. From the point of view of marriage validity, of special significance is also the analysis of confessio iudicialis in the Code of Canon Law from 1917 and 1983. The last part of the author’s reflections is devoted to the analysis of new canon 1678 of the Code of Canon Law, declaring in Pope’s Francis Mitis Iudex Dominus Iesus.